Confidential communications technique based on message block precoder in multi-user MIMO systems - Zhu, Yao; Zhu, Yi-Jun; Zhang, Shui-Lian; Liu, Yong-Gang (Tongxin Xuebao, 2012)
For confidential communications in a multi-user MIMO wiretap channel, though no information regarding the illegitimate receiver was presumed at the transmitter, an artificial interference and a precoding technique based on message block were proposed. Except for confidentiality, the effectivity and efficiency of confidential communications were also taken into consideration. The artificial interference selectively degraded the passive illegitimate receiver' signal while did not effect every legitimate receiver. The precoding technique combined the existed zero-forcing method that used to eliminate the multi-user interference with singular value decomposition (SVD)-based linear precoder so that enhances the efficiency of confidential communications. Simulation result shows that this precoding method degrades the illegitimate receiver' signal to interference plus noise ratio (SINR) even more and enhances the capacity of multi-user MIMO system compared with the precoding method based on single message symbol.